Investigación sobre los diferentes tipos de papa ecuatoriana aplicables para la fritura de profundidad - Domínguez Sosa, Christian Ramiro (2018)
It is very common to think that frying is simply cooking a food in a fatty medium, but this also contains a number of factors such as the type of oil used, temperatures to which it is subjected and its conservation, or different cuts that include they affect the performance of each potato unit, its final qualities after cooking and the visual aspect at the time of assembly; aspects that we will investigate, concluding with several recommendations to take the best advantage of the product and the technique used and thus obtain a frying of high quality. In this document we will discuss the deep-frying technique of the potato, which is a millennial food of Andean origin, always present in the diet of Ecuadorians. Our country is mega diverse because of its location, which is also evident in the great variety of agricultural production. In the case of the potato between natives and produced there are at least four hundred varieties, but very few are commercialized. Going to the main markets of the city, we will find these marketable varieties and through research and observation we will define their organoleptic characteristics and how they act by submitting them to frying techniques, using the same basic recipe. After analyzing the results, we will conclude which is the most suitable variety to obtain a quality fried potato with the criteria of texture, taste, visual appearance and fat absorption. Finally we will present preparations with the best variety of fried potato, using it as garnish through showy assemblies, with different cuts and condiments.